Financial protection from health care spending in Argentina: evolution and distribution (1985-2018) - Virdis, Juan Marcelo (2022)
Financial protection from healthcare spending has become an important objective to be addressed by health systems all over the world. A common strategy used to assess financial protection from health care is to estimate the proportion of the population for which out-of-pocket expenditures made at the moment of receiving health services (OOP) might affect the consumption of other goods and services. To this end, two groups of indicators have been developed: catastrophic health expenditure (CHE) and impoverishing health expenditure (IHE). This work aims to investigate how CHE and IHE evolved in Argentina and how equitable was distributed between 1985 and 2018.